An Al-Ti-Nb-V-B-C intermediate alloy refiner for aluminum-silicon alloy and a preparation method and application thereof
Patent Information
- Application Number
- CN202611131205.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]本发明的目的在于:针对现有两种主流五元中间合金无法同时实现化学界面稳定抗硅毒化、物理颗粒分散稳定的双重缺陷,本发明提供一种Al-Ti-Nb-V-B-C六元铝基中间合金细化剂及其制备方法、应用工艺;通过Ti、Nb、V、B、C种功能元素协同配比,同步实现V元素界面修饰长效抗硅中毒、C元素复合碳化物钉扎抑制颗粒聚集粗化,在高硅、长时间保温工况下维持稳定细化效果,保证铸件组织均匀、力学性能稳定、工艺重现性高
1.解决Al-Ti-Nb-V-B合金颗粒易沉降聚集缺陷,物理分散稳定性大幅提升;
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal material processing technology, specifically relating to a multi-component aluminum-based master alloy grain refiner for refining the grains of cast aluminum-silicon alloys, its preparation method and application. Background Technology
[0002] Grain refinement is a core process for improving the mechanical and casting properties of cast aluminum-silicon alloys. In traditional Al-Ti-B grain refiners, TiB2 particles easily react with silicon-rich melts at the interface, leading to silicon poisoning and rapid loss of the grain refinement effect. The industry has gradually developed multi-component composite grain refinement master alloys, with technological development divided into three generations: The first generation of anti-poisoning systems: Al-Nb-B and Al-VB single systems rely on the high melting point characteristics of NbB2 and VB2 to improve the resistance to silicon poisoning, but the refining efficiency is low and the particles coarsen rapidly at high temperatures. The second-generation binary composite anti-poisoning system: Al-Ti-Nb-B, Al-Ti-VB, Al-Nb-VB quaternary alloys, generate (Ti,Nb)B2 composite boride to optimize the interface structure and improve the resistance to silicon poisoning, but do not solve the physical stability defects of particle sedimentation and agglomeration. The third generation introduces carbon elements to improve the dispersion system: Al-Ti-Nb-BC pentagonal master alloy (patent CN118308630A). By adding C, TiC and NbC carbides are generated to pin the matrix and alleviate the problem of particle segregation and coarsening. However, the system does not contain V elements and lacks interface modification active components. Under the condition of long-term heat preservation of high silicon melt, silicon atoms continue to erode the interface of boride particles, and the long-term anti-silicon poisoning performance has obvious shortcomings.
[0003] Both existing mainstream improvement approaches have irreconcilable technical flaws: Route 1: Al-Ti-Nb-VB pentagonal master alloy, such as patent CN117286355A, an aluminum-based multi-component boride grain refiner resistant to Si poisoning and its preparation method: The system contains V element, which can change the electronic state of the (Ti,Nb)B2 boride surface, forming a silicon atom adsorption energy barrier, resulting in strong chemical interface stability and excellent anti-silicon poisoning effect; however, the system lacks carbon element and lacks fine carbide anchoring phase. The boride particles in the melt are easily precipitated and undergo Ostwald ripening due to density difference and intermolecular forces. The number of effective nucleation particles decreases rapidly with the holding time, resulting in extremely poor physical dispersion stability.
[0004] Route 2 Al-Ti-Nb-BC pentagonal master alloy: It improves particle uniformity and physical dispersion stability by relying on the pinning effect of carbides; however, it lacks the interface modification effect of V element and relies only on the stability of boride itself and the barrier of silicon atoms by the thin layer of carbide. Under long-term high silicon environment, the interface protective layer is easily penetrated, the refining effect decays rapidly with the heat preservation time, and the long-term reliability is insufficient.
[0005] In summary, the industry currently lacks an aluminum-silicon alloy refining intermediate that can simultaneously achieve long-term resistance to silicon poisoning and highly dispersed and stable particle size. Under conditions of high silicon content, long-term heat preservation, and complex castings, the refining effect decays rapidly and the performance reproducibility is poor, which restricts the stable mass production of high-quality aluminum-silicon castings. Summary of the Invention
[0006] The purpose of this invention is to address the dual shortcomings of existing mainstream pentagonal master alloys, which cannot simultaneously achieve chemical interface stability against silicon poisoning and physical particle dispersion stability. This invention provides an Al-Ti-Nb-VBC hexa-aluminum-based master alloy refiner, its preparation method, and application process. Through the synergistic proportion of functional elements Ti, Nb, V, B, and C, it simultaneously achieves long-term anti-silicon poisoning through V element interface modification and C element composite carbide pinning to inhibit particle aggregation and coarsening. It maintains a stable refinement effect under high silicon and long-term heat preservation conditions, ensuring uniform casting structure, stable mechanical properties, and high process reproducibility.
[0007] To achieve the above objectives, the present invention provides the following technical solution: an Al-Ti-Nb-VBC master alloy refiner for aluminum-silicon alloys, comprising the following components by mass percentage: Titanium (Ti): 1.5%-4.5%; Niobium (Nb): 2.0%-7.0%; Vanadium (V): 0.8%-3.0%; Boron (B): 1.0%-4.0%; Carbon (C): 0.1%-1.0%; The total content of unavoidable impurities is <0.2%; The balance is metallic aluminum (Al). Among them, the mass ratio of vanadium to niobium V / Nb = 0.2-0.6; the atomic ratio of boron to carbon B / C = (2:1)-(8:1); The intermediate alloy contains both a (Ti,Nb,V)B2 composite boride phase and a (Ti,Nb,V)C composite carbide phase. The (Ti,Nb,V)C composite carbide is distributed on the surface and in the gaps between the (Ti,Nb,V)B2 composite boride particles in an embedded or attached form.
[0008] As a further aspect of the present invention: the preferred range of each component, by mass percentage, is as follows: Titanium (Ti): 2.5%-3.5%; Niobium (Nb): 3.0%-5.0%; Vanadium (V): 1.2%-2.0%; Boron (B): 2.0%-3.0%; Carbon (C): 0.2%-0.6%; The atomic ratio of boron to carbon is B:1 to 6:1.
[0009] As a further embodiment of the present invention: the product form is any one of ingot crushed particles, wire, or cake-shaped precast blocks; the particle size is 0.2-2mm.
[0010] The preparation method of Al-Ti-Nb-VBC master alloy refiner includes the following steps: S1. Raw material preparation: Weigh industrial pure aluminum ingots, Al-10Ti master alloy, Al-60Nb master alloy, Al-55V master alloy, potassium fluoroborate KBF4, potassium fluorotitanate K2TiF6 and nano-graphite powder mixed composite salt. S2. Basic melt smelting: Pure aluminum ingots are placed in a graphite crucible medium-frequency induction furnace for melting. The temperature is raised to 900-950℃, and preheated Al-Ti, Al-Nb, and Al-V master alloys are added in sequence. The mixture is then stirred electromagnetically until completely dissolved and homogeneous. S3. High-temperature in-situ synthesis reaction: The composite salt, preheated to 300℃, is added to the aluminum melt in batches. Under argon atmosphere protection, the melt temperature is controlled at 920-970℃. Simultaneously, electromagnetic stirring combined with mechanical stirring is used for 30-50 minutes to complete the in-situ generation reaction of borides and carbides. S4. Homogenize and allow to stand: Stop stirring, cool the melt to 850-880℃, and let it stand for 10-15 minutes. S5. Casting: The molten material is poured into a preheated high-speed steel mold at 250-350℃ and quickly solidified to obtain an ingot. S6. Post-processing: The surface oxide layer is removed by turning the ingot, and then it is crushed and screened to obtain the target size finer particles.
[0011] As a further embodiment of the present invention, the carbon source is replaced with any one of carbon nanotubes, graphene-encapsulated salt particles, SiC powder, or methane / acetylene high-temperature pyrolysis carburizing.
[0012] As a further aspect of the present invention: the melting temperature range in step S3 is adjusted to 900-980℃; casting is replaced by continuous casting and atomization powdering process.
[0013] The application of Al-Ti-Nb-VBC master alloy grain refiner in the grain refinement of aluminum-silicon alloys, wherein the silicon content of the aluminum-silicon alloy is 5-20%; the amount of grain refiner added is 0.05%-0.3% of the total mass of the aluminum-silicon alloy melt. Timing of addition: After the aluminum-silicon alloy refining and degassing is completed, add the refining agent when the melt temperature is 740-760℃; After adding, disperse by high-shear mechanical stirring for 3-5 minutes. The melt should be allowed to stand for a maximum of 60 minutes before being poured into shape. In aluminum-silicon alloy melts with a silicon content ≥10%, after adding a grain refiner and holding at a constant temperature for 60 minutes, the average grain size growth rate of α-Al does not exceed 10%.
[0014] Compared with the prior art, the beneficial effects of the present invention are: 1. Solves the defect of easy sedimentation and aggregation of Al-Ti-Nb-VB alloy particles, and significantly improves physical dispersion stability; This invention introduces a controllable amount of carbon element and strictly limits the B / C atomic ratio to generate nanoscale (Ti,Nb,V)C composite carbides in situ, which serve as physical anchors to pin and encapsulate (Ti,Nb,V)B2 boride particles. This effectively suppresses boride sedimentation and Ostwald ripening and coarsening in high-temperature melts, and maintains a high and uniform number density of effective nucleated particles inside the melt under long-term heat preservation.
[0015] 2. It solves the problem of insufficient long-term resistance to silicon poisoning in Al-Ti-Nb-BC alloys, and significantly enhances the chemical interface stability; The system retains a limited amount of V element, and V atoms form an atomic-level modification layer on the surface of composite boride particles, constructing a dense silicon atom diffusion barrier. Even under harsh conditions such as silicon content >12% and heat preservation time exceeding 60 minutes, the nucleation interface remains active, and its long-term reliability against silicon poisoning is far superior to that of V-free carbide systems.
[0016] 3. The synergistic effect of multiple elements produces a synergistic effect of 1+1>2, achieving both long-lasting anti-toxicity and high particle dispersion. Existing technologies can only achieve single-function resistance to silicon poisoning or particle stabilization. This invention integrates two functions, V interface modification and C carbide pinning, into the same hexa-eight alloy system. There is no trade-off in performance, resulting in stable refining effect and significantly extended efficiency.
[0017] 4. Wide process adaptability and high industrial reproducibility; The preparation process temperature, stirring, and casting parameters are controllable and adjustable. The raw materials are all commercially available mature intermediate alloys and chemical auxiliaries, and the production cost is controllable. It is compatible with a full range of aluminum-silicon alloys with 5-20% silicon content. The refining agent can be made into various forms such as granules, wires, and preforms to meet the feeding needs of different casting production lines. Attached Figure Description
[0018] Figure 1 This is a flowchart of the process for preparing the refining agent of the present invention. Detailed Implementation
[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example 1: A refining agent with a Ti content of 1.5% and a low B / C atomic ratio, and its preparation method.
[0020] This embodiment provides an Al-Ti-Nb-VBC master alloy refiner for aluminum-silicon alloys, which consists of the following components by mass percentage: Ti 1.5%, Nb 2.0%, V 0.8%, B 1.0%, C 0.1%, impurities 0.12%, and the balance being Al. The V / Nb ratio is 0.4, and the B / C atomic ratio is 2:1.
[0021] Its preparation method is as follows: S1. Raw material preparation: Weigh the industrial pure aluminum ingot, Al-10Ti master alloy, Al-60Nb master alloy, Al-55V master alloy, potassium fluoroborate KBF4, potassium fluorotitanate K2TiF6 and nano-graphite powder mixed composite salt according to the above component ratio. S2. Basic melt smelting: Industrial pure aluminum ingots are placed in a graphite crucible and melted in a medium-frequency induction furnace. The temperature is raised to 900°C, and preheated Al-Ti, Al-Nb, and Al-V master alloys are added in sequence. The mixture is then stirred electromagnetically until completely dissolved and homogeneous. S3. High-temperature in-situ synthesis reaction: The composite salt, preheated to 300℃, is added to the aluminum melt in batches. Under argon atmosphere protection, the melt temperature is controlled at 920℃. Simultaneously, electromagnetic stirring combined with mechanical stirring is used for 30 min to complete the in-situ generation reaction of borides and carbides. S4. Homogenize and stand: Stop stirring, cool the melt to 850℃, and let it stand for 10 minutes. S5. Casting: The molten material is poured into a high-speed steel mold preheated to 250°C and solidified rapidly to obtain an ingot. S6. Post-processing: The surface oxide layer is removed by turning the ingot, and then crushed and screened to obtain a 0.2-2mm particle refiner.
[0022] Application Test: The grain refiner prepared in this embodiment was added to an aluminum-silicon alloy (Al-10Si) melt with a silicon content of 10%, at a dosage of 0.05% of the total mass of the aluminum-silicon alloy melt. The melt temperature was 740℃ when the material was added, and the mixture was mechanically stirred under high shear for 3 minutes. Samples were taken and cast after holding at this temperature for 10 minutes, 30 minutes, and 60 minutes, respectively. The average grain size of α-Al was determined by metallographic method.
[0023] Experimental results: The average α-Al grain size of the unrefined Al-10Si alloy was 1033 μm; after adding the grain refiner of this embodiment, the average α-Al grain size was 280 μm after 10 min of holding, 290 μm after 30 min, and 298 μm after 60 min. The grain size growth rate within 60 min was (298-280) / 280×100%≈6.4%. After refinement, the grain morphology changed from coarse dendritic grains to fine equiaxed grains. Example 2: A refining agent with a Ti-Nb-VBC pentagonal synergistic optimized formulation and its preparation method.
[0024] This embodiment provides an Al-Ti-Nb-VBC master alloy refiner for aluminum-silicon alloys, which consists of the following components by mass percentage: Ti 3.0%, Nb 4.0%, V 1.6%, B 2.5%, C 0.4%, impurities 0.15%, and the balance being Al. The V / Nb ratio is 0.4, and the B / C atomic ratio is 5:1.
[0025] Its preparation method is as follows: S1. Raw material preparation: Weigh the industrial pure aluminum ingot, Al-10Ti master alloy, Al-60Nb master alloy, Al-55V master alloy, potassium fluoroborate KBF4, potassium fluorotitanate K2TiF6 and nano-graphite powder mixed composite salt according to the above component ratio. S2. Basic melt smelting: Industrial pure aluminum ingots are placed in a graphite crucible and melted in a medium-frequency induction furnace. The temperature is raised to 920°C, and preheated Al-Ti, Al-Nb, and Al-V master alloys are added in sequence. The mixture is then stirred electromagnetically until completely dissolved and homogeneous. S3. High-temperature in-situ synthesis reaction: The composite salt, preheated to 300℃, is added to the aluminum melt in batches. Under argon atmosphere protection, the melt temperature is controlled at 940℃. Simultaneously, electromagnetic stirring combined with mechanical stirring is used for 40 minutes to complete the in-situ generation reaction of borides and carbides. S4. Homogenize and stand: Stop stirring, cool the melt to 860℃, and let it stand for 12 minutes. S5. Casting: The molten material is poured into a high-speed steel mold preheated to 300°C and solidified rapidly to obtain an ingot. S6. Post-processing: The surface oxide layer is removed by turning the ingot, and then crushed and screened to obtain a 0.2-2mm particle refiner.
[0026] Application Test: The grain refiner prepared in this embodiment was added to an aluminum-silicon alloy (Al-15Si) melt with a silicon content of 15%, at a dosage of 0.15% of the total mass of the aluminum-silicon alloy melt. The melt temperature was 750℃ when the material was added, and the mixture was mechanically stirred under high shear for 4 min. Samples were taken and cast after holding at this temperature for 10 min, 30 min, and 60 min, respectively. The average grain size of α-Al was determined by metallographic method.
[0027] Experimental results: The average α-Al grain size of the unrefined Al-15Si alloy was 1500 μm; after adding the grain refiner of this embodiment, the average α-Al grain size was 180 μm after 10 min of holding, 186 μm after 30 min, and 192 μm after 60 min. The grain size growth rate within 60 min was (192-180) / 180×100%≈6.7%. Example 3: A refining agent with a Ti content of 4.5% and a high B / C atomic ratio, and its preparation method.
[0028] This embodiment provides an Al-Ti-Nb-VBC master alloy refiner for aluminum-silicon alloys, which consists of the following components by mass percentage: Ti 4.5%, Nb 7.0%, V 3.0%, B 4.0%, C 1.0%, impurities 0.18%, and the balance being Al. Wherein, V / Nb ≈ 0.43, and the B / C atomic ratio = 8:1.
[0029] Its preparation method is as follows: S1. Raw material preparation: Weigh the industrial pure aluminum ingot, Al-10Ti master alloy, Al-60Nb master alloy, Al-55V master alloy, potassium fluoroborate KBF4, potassium fluorotitanate K2TiF6 and nano-graphite powder mixed composite salt according to the above component ratio. S2. Basic melt smelting: Industrial pure aluminum ingots are placed in a graphite crucible and melted in a medium-frequency induction furnace. The temperature is raised to 950°C, and preheated Al-Ti, Al-Nb, and Al-V master alloys are added in sequence. The mixture is then stirred electromagnetically until completely dissolved and homogeneous. S3. High-temperature in-situ synthesis reaction: The composite salt, preheated to 300℃, is added to the aluminum melt in batches. Under argon atmosphere protection, the melt temperature is controlled at 970℃. Simultaneously, electromagnetic stirring combined with mechanical stirring is used for 50 minutes to complete the in-situ generation reaction of borides and carbides. S4. Homogenize and stand: Stop stirring, cool the melt to 880℃, and let it stand for 15 minutes. S5. Casting: The molten material is poured into a high-speed steel mold preheated to 350°C and solidified rapidly to obtain an ingot. S6. Post-processing: The surface oxide layer is removed by turning the ingot, and then crushed and screened to obtain a 0.2-2mm particle refiner.
[0030] Application Test: The grain refiner prepared in this embodiment was added to a hypereutectic aluminum-silicon alloy (Al-20Si) melt with a silicon content of 20%, at a dosage of 0.30% of the total mass of the aluminum-silicon alloy melt. The melt temperature was 760℃ when the material was added, and the mixture was mechanically stirred under high shear for 5 min. Samples were taken and cast after holding at this temperature for 10 min, 30 min, and 60 min, respectively. The average α-Al grain size and primary silicon size were determined by metallographic analysis.
[0031] Experimental results: The average α-Al grain size of the unrefined Al-20Si alloy was 1800 μm, and the primary silicon was coarse and blocky, with an average size of about 80-120 μm. After adding the refining agent of this embodiment, the α-Al grain size was 210 μm after holding for 10 min, and the primary silicon size was refined to 25-35 μm; the α-Al grain size was 222 μm after holding for 30 min; and the α-Al grain size was 228 μm after holding for 60 min. The grain size growth rate within 60 min was (228-210) / 210×100%≈8.6%.
[0032] Mechanical property testing: The refined Al-20Si alloy was subjected to T6 heat treatment (solution treatment at 535℃ for 4 hours, aging at 170℃ for 6 hours), and the mechanical properties were tested. The tensile strength of the Al-20Si alloy treated with the refining agent in this embodiment was 185 MPa, which was 42% higher than that of the unrefined alloy (130 MPa); the yield strength was 140 MPa, which was 47% higher than that of the unrefined alloy (95 MPa); and the elongation was 1.8%, which was 125% higher than that of the unrefined alloy (0.8%). Example 4: A wire morphology refiner using a high V / Nb ratio and carbon nanotubes as a carbon source, and its preparation method.
[0033] This embodiment provides an Al-Ti-Nb-VBC master alloy refiner for aluminum-silicon alloys, which consists of the following components by mass percentage: Ti 3.0%, Nb 4.0%, V 2.4%, B 2.5%, C 0.4%, impurities 0.15%, and the balance being Al. The V / Nb ratio is 0.6, and the B / C atomic ratio is 5:1. The carbon source is replaced with carbon nanotube powder.
[0034] Its preparation method is as follows: S1-S5 are the same as in Example 2, but in step S1, carbon nanotube powder is used instead of nano-graphite powder as the carbon source; after preparation, the material is directly cast and drawn into a finer wire (diameter φ3-5mm) without crushing and sieving.
[0035] Application Test: The wire refining agent prepared in this embodiment was added to a 15% silicon aluminum-silicon alloy (Al-15Si) melt using a quantitative feeding method. The addition amount was 0.15% (converted mass) of the total mass of the aluminum-silicon alloy melt. The melt temperature was 750℃ when the material was added, and the mixture was mechanically stirred under high shear for 4 min. Samples were taken and cast after holding at this temperature for 10 min, 30 min, and 60 min, respectively. The average α-Al grain size was determined by metallographic method.
[0036] Experimental results: The average α-Al grain size was 179 μm after 10 min of heat treatment, 185 μm after 30 min, and 191 μm after 60 min. The grain size growth rate within 60 min was (191-179) / 179×100%≈6.7%, which is basically consistent with the performance of the particle size refiner in Example 2. This indicates that carbon nanotubes can effectively replace nano-graphite powder as a carbon source, and the wire morphology can also achieve the technical effect of this invention; at the same time, even under the condition that the V / Nb ratio reaches 0.6, the refiner of this invention still maintains good refining effect and long-term stability. Example 5: Effect of different addition amounts on the refining effect of Al-10Si alloy
[0037] This embodiment uses the refining agent composition and preparation process of Example 2, and conducts application tests under different addition amounts.
[0038] Application test: Aluminum-silicon alloy (Al-10Si) melt with 10% silicon content was stirred at 750℃. The amount of refining agent added was set to 0.05%, 0.10%, 0.20%, and 0.30% of the total mass of the aluminum-silicon alloy melt, respectively. The mixture was stirred under high shear for 4 min, held at the temperature for 10 min, and then sampled and poured. The average grain size of α-Al was determined by metallographic method.
[0039] Experimental results: The average α-Al grain size of the unrefined Al-10Si alloy was 1033 μm; it was refined to 280 μm with an addition of 0.05%; to 180 μm with an addition of 0.10%; to 130 μm with an addition of 0.20%; and to 110 μm with an addition of 0.30%. Under all addition conditions, the grain size increase rate after holding at temperature for 60 min did not exceed 10%. Considering both the refining effect and cost, the preferred addition amount is 0.10%-0.20%. Comparative Example 1: Al-Ti-Nb-VB Quaternary Boride Refining Agent without C
[0040] This comparative example provides an Al-Ti-Nb-VB intermediate alloy refiner, which, by mass percentage, consists of the following components: Ti 3.0%, Nb 4.0%, V 1.6%, B 2.5%, no C, with the balance being Al; it is prepared using the same preparation process as in Example 2.
[0041] Application test: 15% silicon aluminum-silicon alloy (Al-15Si) was added at a rate of 0.15% of the total mass of the aluminum-silicon alloy melt. The mixture was added at 750℃ and stirred for 4 min. Samples were taken and cast after holding at this temperature for 10 min, 30 min, and 60 min, respectively. The average grain size of α-Al was determined by metallographic method.
[0042] Experimental results: The α-Al grain size was 195 μm after holding at temperature for 10 min; it coarsened to 250 μm after holding at temperature for 30 min (growth rate of 28%); and it coarsened to 306 μm after holding at temperature for 60 min (growth rate of 57%). Metallographic observation showed that a large number of boride particles settled and accumulated at the bottom of the crucible, and the number of effective nucleation particles in the melt was significantly reduced. Comparative Example 2: Al-Ti-Nb-BC pentagonal refining agent without V element
[0043] This comparative example provides an Al-Ti-Nb-BC intermediate alloy refiner, which, by mass percentage, consists of the following components: Ti 3.0%, Nb 4.0%, B 2.5%, C 0.4%, no V, with the balance being Al; it is prepared using the same preparation process as in Example 2.
[0044] Application test: 15% silicon aluminum-silicon alloy (Al-15Si) was added at a rate of 0.15% of the total mass of the aluminum-silicon alloy melt. The mixture was added at 750℃ and stirred for 4 min. Samples were taken and cast after holding at this temperature for 10 min, 30 min, and 60 min, respectively. The average grain size of α-Al was determined by metallographic method.
[0045] Experimental results: The α-Al grain size was 210 μm after holding at temperature for 10 min; it coarsened to 235 μm after holding at temperature for 30 min (growth rate of 12%); and it coarsened to 277 μm after holding at temperature for 60 min (growth rate of 32%). Metallographic observation revealed silicon atom erosion traces on the surface of some boride particles, indicating a decrease in the activity of the nucleation interface. Comparative Example 3: Commercially available conventional Al-5Ti-1B refining agent
[0046] This comparative example uses commercially available Al-5Ti-1B refining agent as the comparative example. It consists of the following components by mass percentage: Ti 5.0%, B 1.0%, and the balance being Al.
[0047] Application test: 10% silicon aluminum-silicon alloy (Al-10Si) was added at a rate of 0.20% of the total mass of the aluminum-silicon alloy melt. The mixture was added at 750℃ and stirred for 4 min. Samples were taken and cast after holding at this temperature for 10 min, 30 min, and 60 min, respectively. The average grain size of α-Al was determined by metallographic method.
[0048] Experimental results: The α-Al grain size was 320 μm after holding for 10 min; it coarsened to 480 μm after holding for 30 min (growth rate of 50%); and it coarsened to 650 μm after holding for 60 min (growth rate of 103%). Comparison of data from each embodiment and comparative example
[0049] The microstructure, grain size, and mechanical properties of the aluminum-silicon alloy samples prepared by the refining agents in Examples 1-5 and Comparative Examples 1-3 and their treatments were observed, and the specific testing methods are as follows: 1. Microstructure observation and grain size determination
[0050] After grinding and polishing, the metallographic samples were etched with a 0.5% hydrofluoric acid aqueous solution, and the microstructure was observed under an optical microscope. The average grain size of α-Al and the size of primary silicon were determined according to GB / T 6394-2017 "Method for Determination of Average Grain Size of Metals", using the cross-section method. At least 5 fields of view were randomly selected for each group of samples, and the arithmetic mean was taken. 2. Refine the performance evaluation indicators
[0051] The refinement rate is calculated using the following formula: Refinement rate = (Unrefined grain size - Refined grain size) / Unrefined grain size × 100% The grain size growth rate is calculated using the following formula: Growth rate = (Grain size at t min holding time - Grain size at 10 min holding time) / Grain size at 10 min holding time × 100% (t = 30 or 60) 3. Mechanical property testing
[0052] Mechanical property tests were conducted on a universal testing machine in accordance with GB / T 228.1-2021 "Metallic materials - Tensile testing - Part 1: Test method at room temperature". The tensile rate was 2 mm / min, and each group had no less than 3 specimens. The average value was taken.
[0053] The results are shown in Table 1 below:
[0054] In summary, Example 1 used a low-content formulation of Ti, V, B, and C with a B / C atomic ratio of 2:1; Example 3 used a high-content formulation of Ti, Nb, V, B, and C with a B / C atomic ratio of 8:1; Example 2 used a formulation with moderate content of each element; and Example 4 used a formulation with a V / Nb ratio of 0.6. Under all formulation conditions, the grain size growth rate over 60 minutes remained between 6.4% and 8.6%, indicating that the present invention can achieve good grain refinement and long-term stability within the composition range described in claim 1.
[0055] As shown in Examples 1-5, the Al-Ti-Nb-VBC grain refiner of the present invention exhibits excellent grain refinement effects on aluminum-silicon alloys with different silicon contents (10%-20%). Within the addition range of 0.05%-0.30%, the α-Al grains can be refined from over 1000 μm to 110-298 μm, achieving a refinement rate of 70%-90%.
[0056] The grain size growth rate of the Al-Ti-Nb-VBC grain refiner of this invention did not exceed 10% within a 60-minute holding time, which is far superior to Comparative Example 1 (Al-Ti-Nb-VB without C, 57%), Comparative Example 2 (Al-Ti-Nb-BC without V, 32%), and Comparative Example 3 (Al-5Ti-1B, 103%). This indicates that the present invention achieves a balance between "long-lasting resistance to silicon poisoning" and "highly dispersed and stable particles" through the dual synergistic effect of interface modification by V and carbide pinning by C. Comparative Example 1 (containing V but without C) showed a 57% growth rate over 60 minutes, and Comparative Example 2 (containing C but without V) showed a 32% growth rate over 60 minutes. The Al-Ti-Nb-VBC of this invention, which contains both V and C, showed a growth rate of only 6.7% over 60 minutes (Example 2), far lower than the two comparative examples, demonstrating a significant synergistic effect between the "interface modification" function of V and the "pinning and stabilizing" function of C.
[0057] Furthermore, the mechanical property test in Example 3 showed that the tensile strength of the refined Al-20Si alloy increased by 42% and the elongation increased by 125%. Example 4 showed that the carbon source can be replaced with carbon nanotubes and the product form can be wire, without affecting the refining effect, indicating that the present invention has good potential for industrial production.
[0058] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A refining agent for Al-Ti-Nb-VBC master alloys of aluminum-silicon alloys, characterized in that, It contains the following components by weight percentage: Titanium (Ti): 1.5%-4.5%; Niobium (Nb): 2.0%-7.0%; Vanadium (V): 0.8%-3.0%; Boron (B): 1.0%-4.0%; Carbon (C): 0.1%-1.0%; The total content of unavoidable impurities is <0.2%; The balance is metallic aluminum (Al). Among them, the mass ratio of vanadium to niobium V / Nb = 0.2-0.6; the atomic ratio of boron to carbon B / C = (2:1)-(8:1); The intermediate alloy contains both a (Ti,Nb,V)B2 composite boride phase and a (Ti,Nb,V)C composite carbide phase. The (Ti,Nb,V)C composite carbide is distributed on the surface and in the gaps between the (Ti,Nb,V)B2 composite boride particles in an embedded or attached form.
2. The Al-Ti-Nb-VBC master alloy refiner for aluminum-silicon alloys according to claim 1, characterized in that, The preferred ranges for each component, by mass percentage, are as follows: Titanium (Ti): 2.5%-3.5%; Niobium (Nb): 3.0%-5.0%; Vanadium (V): 1.2%-2.0%; Boron (B): 2.0%-3.0%; Carbon (C): 0.2%-0.6%; The atomic ratio of boron to carbon is B:1 to 6:
1.
3. The Al-Ti-Nb-VBC master alloy refiner for aluminum-silicon alloys according to claim 1, characterized in that, The product can be in the form of any one of the following: crushed ingot particles, wire, or pre-formed cake; the particle size is 0.2-2mm.
4. A method for preparing the Al-Ti-Nb-VBC intermediate alloy refining agent according to any one of claims 1-3, characterized in that, Includes the following steps: S1. Raw material preparation: Weigh industrial pure aluminum ingots, Al-10Ti master alloy, Al-60Nb master alloy, Al-55V master alloy, potassium fluoroborate KBF4, potassium fluorotitanate K2TiF6 and nano-graphite powder mixed composite salt. S2. Basic melt smelting: Pure aluminum ingots are placed in a graphite crucible medium-frequency induction furnace for melting. The temperature is raised to 900-950℃, and preheated Al-Ti, Al-Nb, and Al-V master alloys are added in sequence. The mixture is then stirred electromagnetically until completely dissolved and homogeneous. S3. High-temperature in-situ synthesis reaction: The composite salt, preheated to 300℃, is added to the aluminum melt in batches. Under argon atmosphere protection, the melt temperature is controlled at 920-970℃. Simultaneously, electromagnetic stirring combined with mechanical stirring is used for 30-50 minutes to complete the in-situ generation reaction of borides and carbides. S4. Homogenize and allow to stand: Stop stirring, cool the melt to 850-880℃, and let it stand for 10-15 minutes. S5. Casting: The molten material is poured into a preheated high-speed steel mold at 250-350℃ and quickly solidified to obtain an ingot. S6. Post-processing: The surface oxide layer is removed by turning the ingot, and then it is crushed and screened to obtain the target size finer particles.
5. The preparation method according to claim 4, characterized in that, The carbon source can be replaced by any one of the following: carbon nanotubes, graphene-encapsulated salt particles, SiC powder, or methane / acetylene high-temperature pyrolysis carburizing.
6. The preparation method according to claim 4, characterized in that, The melting temperature range in step S3 is adjusted to 900-980℃; casting is replaced by continuous casting and atomization powdering process.
7. The application of the Al-Ti-Nb-VBC master alloy refiner according to any one of claims 1-3 in grain refinement of aluminum-silicon alloys, characterized in that: The silicon content of the aluminum-silicon alloy is 5-20%; the amount of refining agent added is 0.05%-0.3% of the total mass of the aluminum-silicon alloy melt. Timing of addition: After the aluminum-silicon alloy refining and degassing is completed, add the refining agent when the melt temperature is 740-760℃; After adding, disperse by high-shear mechanical stirring for 3-5 minutes. The melt should be allowed to stand for a maximum of 60 minutes before being poured into shape. In aluminum-silicon alloy melts with a silicon content ≥10%, after adding a grain refiner and holding at a constant temperature for 60 minutes, the average grain size growth rate of α-Al does not exceed 10%.